A complete course of photodynamic therapy reduced the risk of malignant transformation of oral leukoplakia - Yansong Song; Fan Tang; Jiaxin Liu; Dan Yang; Jiongke Wang; Xiaobo Luo; Yu Zhou; Xin Zeng; Hao Xu; Qianming Chen; Hongxia Dan (Photodiagnosis and Photodynamic Therapy, 2024)
Background: Photodynamic therapy (PDT) has shown good short-term efficacy in the treatment of oral leukoplakia (OLK). However, the malignant transformation of OLK was seldom evaluated in most PDT studies. Therefore, this study evaluated the effect of PDT on the risk of malignant transformation of OLK. Methods: Kaplan-Meier survival analysis, COX regression, and sensitivity analysis were used to evaluate the effects of PDT on the risk of malignant transformation of OLK. Subgroup analyses were performed to explore the role of PDT in OLK patients with different clinical characteristics. Results: OLK patients with older age (HR=1.032, P = 0.018) and non-homogeneous lesion (HR=2.104, P = 0.044) had higher risk of malignant transformation. Patients who had finished a complete course of PDT (HR=0.305, P = 0.006) had a significant lower risk of malignant transformation, while those who hadn't finished a complete course of PDT (HR=0.692, P = 0.352) cannot be considered to have such a protective effect. In the subgroup analyses, complete PDT course showed a significant protective effect on malignant transformation of OLK in patients with female sex, no smoking or drinking habits, non-homogeneous lesions, lesions on oral mucosa outside the dangerous region, and any grade of epithelial dysplasia. Conclusions: A complete course of PDT could significantly reduce the risk of malignant transformation of OLK, especially in those patients with risk factors of malignant transformation.